Characterization of methanotrophic community and activity in landfill cover soils under dimethyl sulfide stress. (15th April 2023) - Wang, Jing; Wang, Chen; Chu, Yi-Xuan; Tian, Guangming; He, Ruo
Graphical abstract: Highlights: Methanotrophs can oxidize CH4, but also metabolize sulfur compounds. DMS-S is mainly oxidized to SO4 2- in landfill cover soil. High DMS can inhibit CH4 oxidation, decrease the abundance of pmoA and mmoX. Methylobacter and Crenothrix may play a crucial role in metabolizing CH4 and DMS. Abstract: Landfill cover soil is the environmental interface between landfills and the atmosphere and plays an important role in mitigating CH4 emission from landfills. Here, stable isotope probing microcosms with CH4 or CH4 and dimethyl sulfide (DMS) were carried out to characterize activity and community structure of methanotrophs in landfill cover soils under DMS stress. The CH4 oxidation activity in the landfill cover soils was not obviously influenced at the DMS concentration of 0.05%, while it was inhibited at the DMS concentrations of 0.1% and 0.2%. DMS-S was mainly oxidized to sulfate (SO4 2- ) in the landfill cover soils. In the landfill cover soils, DMS could inhibit the expression of bacteria and decrease the abundances of pmoA and mmoX genes, while it could prompt the expression of pmoA and mmoX genes. γ- Proteobacteria methanotrophs including Methylocaldum, Methylobacter, Crenothrix and unclassified Methylococcaceae and α- Proteobacteria methanotrophs Methylocystis dominated in assimilating CH4 in the landfill cover soils. Of them, Methylobacter and Crenothrix had strong tolerance to DMS or DMS could promote the growth and activity of Methylobacter and Crenothrix, while Methylocaldum had weak tolerance to DMS and showed an inhibitory effect. Metagenomic analyses showed that methanotrophs had the genes of methanethiol oxidation and could metabolize CH4 and methanethiol simultaneously in the landfill cover soils. These findings suggested that methanotrophs might metabolize sulfur compounds in the landfill cover soils, which may provide the potential application in engineering for co-removal of CH4 and sulfur compounds.